Collectivity in Small Collision Systems: An Initial-State Perspective - Sören Schlichting; Prithwish Tribedy (Advances in High Energy Physics)
Measurements of multiparticle correlations in the collisions of small systems such as p+p, p/d/3He+A show striking similarity to the observations in heavy-ion collisions. A number of observables measured in the high-multiplicity events of these systems resemble features that are attributed to collectivity driven by hydrodynamics. However, alternative explanations based on initial-state dynamics are able to describe many characteristic features of these measurements. In this brief review, we highlight some of the recent developments and outstanding issues in this direction.